Shape memory super-hydrophobic anticorrosive coating for maritime work metal as well as preparation method and application of shape memory super-hydrophobic anticorrosive coating
By using electrospinning technology using bisphenol A resin and nanofiber composite coating on the metal surface of marine engineering, combined with spraying technology of modified diatomaceous earth and oily epoxy resin, shape memory superhydrophobic anticorrosion coating was prepared, and the solution was solved The existing coatings are prone to cracking, poor hydrophobic properties and short life, achieving efficient corrosion protection and multiple self-healing protection.
Patent Information
- Application Number
- CN202411135668.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-19
AI Technical Summary
The existing marine engineering metal anticorrosion coatings are prone to cracks, have easy hydrophobic properties, short service life, and the traditional superhydrophobic coatings have poor mechanical properties, which cannot provide long-term protection.
The electrospinning technology of bisphenol A resin and nanofiber composite coating is prepared by using electrospinning technology of modified diatomaceous earth and oily epoxy resin, which has self-healing, wear resistance, Resistance to peel and multiple self-healing properties.
It improves the protective effect of the coating, extends durability, reduces the risk of corrosion, enhances the repulsion and mechanical properties of water molecules, and achieves long-lasting superhydrophobic properties and multiple self-healing capabilities.
Smart Images

Figure CN119119823A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of marine engineering metal anti-corrosion, and specifically relates to a shape memory super hydrophobic anti-corrosion coating for marine engineering metal, and a preparation method and application thereof. Background Art
[0002] The corrosion problem of metals has always been an issue worthy of attention. With the continuous improvement of modern metal anti-corrosion requirements, many new anti-corrosion technologies have emerged. Organic coatings are the most common and effective protection technology for metal materials and are widely used in various fields such as ocean, chemical industry, transportation, and ships. With the continuous improvement of coating technology, new anti-corrosion coatings have been developed. Among them, organic coatings will inevitably produce defects such as micropores and cracks due to the volatilization of solvents during the curing process. Some small molecular corrosive media (such as water, chloride ions, etc.) will reach the metal matrix through these cracks or defects, causing metal corrosion. Therefore, it is necessary to increase the coating's repellency to aqueous media and reduce the contact area and contact time between the coating and the corrosive medium to improve the coating's corrosion resistance. At the same time, giving the coating self-healing properties is also one of the important means to increase the service life of the coating.
[0003] In addition, due to the poor mechanical properties of traditional super-hydrophobic coatings, the surface micro-nanostructure is easily damaged, resulting in the failure of hydrophobic properties, and therefore cannot provide long-term protection for the coating.
[0004] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention
[0005] The purpose of the present invention is to provide a shape memory super hydrophobic anti-corrosion coating for marine engineering metals, and a preparation method and application thereof, so as to help solve or improve at least one of the problems of the anti-corrosion coating on the surface of marine engineering metals being prone to cracking, the hydrophobic performance being prone to failure, and the service life being short, so as to help improve the protective effect of the anti-corrosion coating applied to marine engineering metals.
[0006] In order to achieve the above-mentioned purpose, the present invention provides the following technical scheme: a method for preparing a shape memory super-hydrophobic anti-corrosion coating for marine metal, comprising the following steps: (1) preparation of bisphenol A resin coating: bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether and n-n-decylamine are mixed uniformly to obtain a resin coating solution, and the resin coating solution is coated on a metal substrate. After the resin coating solution reaches a surface dry state, a metal substrate coated with a bisphenol A resin coating is obtained; the mass ratio of the bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether and n-n-decylamine is (1-4):(1-3):1; (2) preparation of a nanofiber composite coating: electrostatic spinning is performed on the surface of the metal substrate coated with the bisphenol A resin coating to obtain the nanofiber composite coating; The components of the electrospinning solution include a first solvent and polycaprolactone; (3) Preparation of a shape memory super hydrophobic anti-corrosion coating: spraying the super hydrophobic coating solution on the surface of the nanofiber composite coating to obtain the shape memory super hydrophobic anti-corrosion coating; the components of the super hydrophobic coating solution include modified diatomaceous earth, oily epoxy resin, a curing agent and a second solvent; the modified diatomaceous earth is prepared by a method comprising the following steps: dispersing natural diatomaceous earth in a third solvent, stirring evenly and then adding octadecyltrimethoxysilane, first heating to a first temperature and stirring for a first time, then continuing to stir at room temperature for a second time, filtering, washing and drying to obtain the modified diatomaceous earth; the mass ratio of the natural diatomaceous earth to the octadecyltrimethoxysilane is 1:1-10:1.
[0007] Preferably, in step (3), the mass ratio of the oily epoxy resin to the modified diatomaceous earth is 1:2-1:10, the mass ratio of the oily epoxy resin to the curing agent is 2:1-1:1, and the mass ratio of the oily epoxy resin to the second solvent is 1:8-1:16; and the second solvent is anhydrous ethanol.
[0008] Preferably, in the preparation process of the modified diatomaceous earth, the mass volume ratio of the natural diatomaceous earth to the third solvent is 1:(11-12), the mass of the natural diatomaceous earth is measured in g, and the volume of the third solvent is measured in mL; the first temperature is 35-60°C, the first time is 8-16h; the second time is 6-12h; and the third solvent is ethanol.
[0009] Preferably, the spinning solution is prepared by a method comprising the following steps: A. mixing N,N-dimethylformamide and dichloromethane at a temperature of 18-25°C and a humidity of 20%-30% to obtain a first solvent; B. adding polycaprolactone to the first solvent; C. raising the temperature to 35-60°C and continuing stirring for 12-18 hours to obtain the spinning solution.
[0010] Preferably, in the first solvent, the mass ratio of N,N-dimethylformamide to dichloromethane is 1:1-1:6; and the mass ratio of the polycaprolactone to the first solvent is (2-6):25.
[0011] Preferably, in step (2), the preparation of the nanofiber composite coating includes the following steps: fixing a syringe filled with spinning solution on an electrostatic coaxial spinning machine, connecting the coaxial needle to positive and negative power supplies, covering a collector with a piece of aluminum foil, fixing a metal substrate coated with a bisphenol A resin coating on the aluminum foil, and performing electrostatic spinning; the voltage of the electrostatic spinning is 7-12 kV, the pushing speed of the injection pump is 0.4-0.8 mm / min, and the spinning time is 20-40 min; the electrostatic spinning is performed under a humidity of 20%-30%.
[0012] Preferably, in step (3), the superhydrophobic coating solution is sprayed on the surface of the nanofiber composite coating by air pressure spraying, the air pressure during the air pressure spraying is 0.5-1.2atm, the spray gun is 6-10cm away from the coating surface, the spraying time is 15-25s, and the number of spraying times is 1-3 times.
[0013] Preferably, the metal matrix is made of at least one of carbon steel, magnesium alloy, aluminum alloy, copper and titanium alloy.
[0014] The present invention also provides a shape memory super hydrophobic anti-corrosion coating for marine engineering metals, which adopts the following technical scheme: a shape memory super hydrophobic anti-corrosion coating for marine engineering metals, characterized in that the shape memory super hydrophobic anti-corrosion coating for marine engineering metals is prepared by the method described above.
[0015] The present invention also provides a marine metal equipment, which adopts the following technical solution: a marine metal equipment, the surface of which is provided with the shape memory super hydrophobic anti-corrosion coating as described above.
[0016] Beneficial effects:
[0017] In the preparation method of the shape memory super hydrophobic anticorrosion coating for marine metal of the present invention, the nanofiber composite coating obtained by electrostatic spinning on the surface of the metal substrate coated with the resin coating, the polycaprolactone nanofiber in the nanofiber composite coating is combined with bisphenol A epoxy resin, so that the nanofiber composite coating has the performance of self-healing, and then the coating solution containing modified diatomaceous earth and oily epoxy resin is sprayed on the surface of the nanofiber composite coating, and the shape memory super hydrophobic anticorrosion coating for marine metal can be obtained after curing. The shape memory super hydrophobic anticorrosion coating for marine metal prepared by the method of the present invention helps to solve or improve the defects of poor mechanical properties of super hydrophobic coating, few repair times of self-repairing coating, low efficiency, etc. in the prior art; the preparation method of the shape memory super hydrophobic anticorrosion coating for marine metal of the present invention is simple in process and low in cost, and the shape memory super hydrophobic anticorrosion coating for marine metal prepared also has multiple excellent properties such as high impedance, wear resistance, peeling resistance and self-healing, and has outstanding durability, and has great application prospects in practical applications such as marine corrosion protection.
[0018] The nanofiber composite coating (combined by a resin coating and a nanofiber membrane obtained by electrospinning a spinning solution) in the shape memory super-hydrophobic anti-corrosion coating for marine metals of the present invention can not only improve the overall flexibility of the coating, but also fill the micropore defects in the coating, and at the same time give the coating a self-healing function, thereby preventing and extending the durability of the super-hydrophobic coating and delaying the occurrence of the corrosion process.
[0019] The surface of the shape memory super hydrophobic anti-corrosion coating for marine engineering metal of the present invention presents a higher contact angle, a lower sliding angle, and a lasting super hydrophobic property; the nanofiber composite coating has a shape memory effect, and when the coating is damaged, it only needs to be heated (for example, heated at 50°C for 2 hours) to restore the original surface morphology (this allows the shape memory super hydrophobic anti-corrosion coating for marine engineering metal of the present invention to significantly reduce the contact area and contact time between the coating and water molecules during use, which is beneficial to preventing corrosive media from penetrating the coating).
[0020] The shape memory super hydrophobic anti-corrosion coating for marine engineering metals of the present invention has a wide range of applications, has good adhesion, water resistance, and salt water penetration resistance after being cured into a film, and has multiple self-healing properties, a simple process, and has excellent anti-corrosion effects and lasting protective capabilities. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:
[0022] Figure 1The scanning electron microscope images of the coatings provided in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention; wherein (a) is a scanning electron microscope image of the coating of Comparative Example 1, (b) is a scanning electron microscope image of the coating of Comparative Example 2, and (c) is a scanning electron microscope image of the coating of Example 1;
[0023] Figure 2 Laser confocal images of the coatings provided in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention; wherein (a) is a laser confocal image of the coating of Comparative Example 1, (b) is a laser confocal image of the coating of Comparative Example 2, and (c) is a laser confocal image of the coating of Example 1;
[0024] Figure 3 The water contact angle diagrams of the coatings provided in Example 1 and Comparative Example 2 of the present invention at different times; wherein (a) is the water contact angle diagram of the coating of Example 1, and (b) is the water contact angle diagram of the coating of Comparative Example 2;
[0025] Figure 4 The pull-out test result diagram of the coating provided in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;
[0026] Figure 5 The Bode diagrams and Nyquist diagrams of the coatings provided in Example 1 and Comparative Example 1 of the present invention after immersion for 45 days are shown; wherein (a) is the Bode diagram of the modulus, (b1) is the Nyquist diagram, and (b2) is a partial enlarged diagram of (b1).
[0027] Figure 6 The microscopic morphology diagrams are the wear resistance test results of the coating provided in Example 1 of the present invention; wherein, (a1) is the microscopic morphology diagram after 0 wear times, (a2) is the microscopic morphology diagram after 60 wear times, (a3) is the microscopic morphology diagram after 120 wear times, and (a4) is the microscopic morphology diagram after 160 wear times.
[0028] Figure 7 The self-healing result diagram of the coating of Example 1 of the present invention is shown in Figure 1. (a) is a laser confocal image of Example 1 after destruction, and (b) is a laser confocal image of Example 1 after heating and healing.
[0029] Figure 8 The test result diagrams are of the EIS test conducted after the coating of Example 1 of the present invention was damaged and then self-healed by heating; wherein (a) is the Bode diagram of the modulus value, (b1) is the Nyquist diagram, and (b2) is a partial enlarged diagram of (b1). DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0031] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0032] The present invention aims at the problems that the anti-corrosion coating on the surface of marine engineering metal is prone to cracking, the hydrophobic performance is easy to fail and the service life is short. The inventor creatively thinks that it would be a new attempt to introduce the self-repairing function into the super-hydrophobic coating, which helps to improve the coating's repellency to aqueous media while having self-repairing properties. The two functions work together to better protect the metal. Based on this, the present invention provides a method for preparing a shape memory super-hydrophobic anti-corrosion coating for marine engineering metals, which helps to solve at least one of the above problems.
[0033] The method for preparing a shape memory super hydrophobic anti-corrosion coating for marine metal according to an embodiment of the present invention comprises the following steps:
[0034] (1) Preparation of bisphenol A resin coating:
[0035] Bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether and n-n-decylamine are uniformly mixed to obtain a bisphenol A resin coating solution, and the resin coating solution is coated on a metal substrate. After the resin coating solution reaches a surface dry state, a metal substrate coated with a bisphenol A resin coating is obtained; the mass ratio of bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether and n-n-decylamine is (1-4):(1-3):1 (for example, 1:1:1, 4:1:1, 3:1:1, 2:1:1, 1:3:1, 1:2:1 or 2:2:1, etc.);
[0036] (2) Preparation of nanofiber composite coating:
[0037] Electrospinning is performed on the surface of a metal substrate coated with a resin coating to obtain a nanofiber composite coating; the components of the electrospinning solution include a first solvent and polycaprolactone;
[0038] (3) Preparation of shape memory superhydrophobic anticorrosion coating:
[0039] A super-hydrophobic coating solution is sprayed on the surface of the nanofiber composite coating to obtain a shape memory super-hydrophobic anti-corrosion coating; the components of the super-hydrophobic coating solution include modified diatomaceous earth, an oily epoxy resin, a curing agent and a second solvent; wherein the modified diatomaceous earth is prepared by a method comprising the following steps: natural diatomaceous earth is dispersed in a third solvent, octadecyltrimethoxysilane is added after stirring evenly, the temperature is first raised to a first temperature and stirred for a first time, and then stirring is continued at room temperature for a second time, filtering, washing and drying to obtain the modified diatomaceous earth; the mass ratio of natural diatomaceous earth to octadecyltrimethoxysilane is 1:1-10:1.
[0040] Wherein, the bisphenol A resin coating obtained in step (1) has certain self-healing properties; step (2) by selecting polycaprolactone, and using N, N dimethylformamide and dichloromethane as solvents for spinning solution, the nanofiber membrane obtained by electrostatic spinning can be made to have self-healing properties; the nanofiber composite coating obtained by the bisphenol A resin coating and the nanofiber membrane obtained by electrostatic spinning of the present invention can better combine with the metal matrix while having self-healing properties, and also help to better achieve the attachment of hydrophobic particles in the super-hydrophobic coating solution, and then better improve the life of the shape memory super-hydrophobic anti-corrosion coating for marine metal prepared by the present invention. In addition, the mass ratio of bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether and n-n-decylamine in the bisphenol A resin coating solution will affect the self-healing temperature of the bisphenol A resin coating. The performance of the modified diatomaceous earth used in the super-hydrophobic coating solution is related to the dosage ratio of natural diatomaceous earth and octadecyltrimethoxysilane, which will significantly affect the water contact angle of the prepared shape memory super-hydrophobic anti-corrosion coating for marine metal (when the water contact angle is greater than 150°, the coating has super-hydrophobicity); the oily epoxy resin in the present invention can improve the mechanical properties of the coating (for example, adhesion strength, etc.).
[0041] The nanofiber composite coating of the present invention is composed of a bisphenol A resin coating and a nanofiber film obtained by electrostatic spinning of a spinning solution containing polycaprolactone, which can not only improve the overall flexibility of the coating, but also help to fill the micropore defects in the coating, and the nanofiber composite coating can also have a self-healing effect (helping to extend the durability of the super-hydrophobic coating and delay the occurrence of the corrosion process); after that, the super-hydrophobic coating solution containing modified diatomaceous earth and oily epoxy resin is sprayed on the surface of the nanofiber composite coating, and the shape memory super-hydrophobic anti-corrosion coating for marine metal of the present invention can be obtained (the super-hydrophobic coating solution can make the coating surface of the present invention present a higher contact angle, a lower sliding angle, and a lasting super-hydrophobic performance after spraying). The shape memory super-hydrophobic anti-corrosion coating for marine metal prepared by the method of the present invention not only helps to solve or improve the poor mechanical properties of the super-hydrophobic coating, can not achieve self-repair or self-repair times, low efficiency and other defects, but also has multiple excellent performances such as high impedance, wear resistance, peeling resistance and self-healing, outstanding durability, and has a huge application prospect in practical applications such as marine engineering metal corrosion protection.
[0042] In a preferred embodiment of the method for preparing a shape memory superhydrophobic anti-corrosion coating for marine metal of the present invention, in step (3), the mass ratio of the oily epoxy resin to the modified diatomaceous earth is 1:2-1:10 (for example, 1:2, 1:4, 1:6, 1:8 or 1:10), the mass ratio of the oily epoxy resin to the curing agent is 2:1-1:1 (for example, 2:1, 1.5:1 or 1:1), and the mass ratio of the oily epoxy resin to the second solvent is 1:8-1:16 (for example, 1:8, 1:10, 1:12, 1:14, 1:15 or 1:16); the second solvent is anhydrous ethanol. Among them, if the amount of modified diatomaceous earth used is too much, the modified diatomaceous earth cannot be firmly bonded to the surface of the fiber membrane, and the modified diatomaceous earth in the cured superhydrophobic layer will easily fall off, so the coating cannot maintain the superhydrophobic properties for a long time; if the ratio of oily epoxy resin and curing agent is too high, the modified diatomaceous earth will be completely coated by the oily epoxy resin, and the superhydrophobicity of the coating will be reduced.
[0043] In a preferred embodiment of the method for preparing a shape memory superhydrophobic anti-corrosion coating for marine metal of the present invention, during the preparation of the modified diatomaceous earth, the mass volume ratio of natural diatomaceous earth to the third solvent is 1: (11-12) (for example, 1: 11, 1: 11.2, 1: 11.4, 1: 11.6, 1: 11.8 or 1: 12), the mass of natural diatomaceous earth is measured in g, and the volume of the third solvent is measured in mL; the first temperature is 35-60°C (for example, 35°C, 45°C, 55°C or 60°C), the first time is 8-16h (for example, 8h, 10h, 12h, 14h or 16h); the second time is 6-12h (for example, 6h, 8h, 10h or 12h); the third solvent is ethanol. Among them, in the process of modifying natural diatomite, the amount of solvent used will affect the dispersion effect of natural diatomite and the concentration of octadecyltrimethoxysilane, and then affect the modification effect of natural diatomite; if the amount of the third solvent is not appropriate, it will cause the water contact angle of the shape memory super hydrophobic anti-corrosion coating for marine metal of the present invention to decrease, and the hydrophobic performance will decrease; when the amount ratio of natural diatomite to the third solvent is within the range defined in the preferred embodiment of the present invention, it is helpful to prepare a shape memory super hydrophobic anti-corrosion coating for marine metal with a water contact angle of more than 150°. If the first temperature is too low, the hydrolysis condensation reaction will not be thorough, so the modification process is slow and inefficient; if the first time is too long, the reaction cannot be completed, thereby reducing the modification efficiency, and the super hydrophobicity of the obtained modified diatomite is not persistent; the second time of stirring at room temperature is too short, which will cause the stability of the modified diatomite to decrease, and it is impossible to provide super hydrophobicity for the coating for a long time.
[0044] In a preferred embodiment of the method for preparing a shape memory superhydrophobic anti-corrosion coating for marine engineering metals of the present invention, the spinning solution is prepared by a method comprising the following steps: A. Mixing N,N-dimethylformamide and dichloromethane at a temperature of 18-25°C (for example, 18°C, 20°C, 22°C or 25°C) and a humidity of 20%-30% (for example, 20%, 24%, 26%, 28% or 30%) to obtain a first solvent; B. Adding polycaprolactone to the first solvent; C. Raising the temperature to 35-60°C (for example, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C), and continuing stirring for 12-18h (for example, 12h, 14h, 16h or 18h) to obtain the spinning solution. The temperature in step C (the temperature should not be too high, as too high a temperature may cause the polycaprolactone to become ineffective and unusable) and the stirring time are appropriate to fully dissolve the polycaprolactone and increase the dissolution rate of the polycaprolactone so that the spinning solution can meet the needs of electrospinning.
[0045] In a preferred embodiment of the method for preparing a shape memory super hydrophobic anticorrosive coating for marine metal of the present invention, the first solvent includes N, N dimethylformamide and dichloromethane, and the mass ratio of N, N dimethylformamide and dichloromethane is 1: 1-1: 6 (for example, 1: 1, 1: 2, 1: 3, 1: 4, 1: 5 or 1: 6); the mass ratio of polycaprolactone to the first solvent is (2-6): 25 (for example, 2: 25, 3: 25, 4: 25, 5: 25 or 6: 25). Among them, the amount of the first solvent in the spinning solution and the amount ratio of N, N dimethylformamide and dichloromethane in the first solvent will affect the self-healing temperature of the nanofiber membrane obtained by electrospinning (specifically, the amount and ratio of the first solvent will affect the solubility of polycaprolactone, and the molecular chain of the polymer is large enough, so the solubility change will inevitably affect the glass transition temperature of polycaprolactone; in addition, the first solvent will also affect the fiber morphology obtained by electrospinning).
[0046] In a preferred embodiment of the method for preparing a shape memory super-hydrophobic anti-corrosion coating for marine metal of the present invention, in step (2), the preparation of the nanofiber composite coating comprises the following steps: fixing a syringe containing a spinning solution on an electrostatic coaxial spinning machine, connecting the coaxial needle to a positive and negative power supply, covering a collector with an aluminum foil, fixing a metal substrate coated with a bisphenol A resin coating on the aluminum foil, and performing electrostatic spinning; the voltage of the electrostatic spinning is 7-12 kV (for example, 7 kV, 8 kV, 10 kV or 12 kV), The pushing speed of the injection pump is 0.4-0.8 mm / min (for example, 0.5 mm / min, 0.6 mm / min or 0.7 mm / min), and the spinning time is 20-40 min (for example, 25 min, 30 min, 35 min or 40 min); the electrospinning is carried out at a temperature of 18-25°C (for example, 20°C, 22°C, 24°C, 26°C or 28°C) and a humidity of 20%-30% (for example, 22%, 24%, 26%, 28% or 30%). Among them, if the voltage of electrospinning is too low, the electrostatic force will be insufficient to stretch the polymer molecular chain into filaments, so electrospinning cannot proceed normally; if the voltage of electrospinning is too high, the spinning solution will not be fully stretched and will be collected on the drum in the form of droplets; if the injection speed of the injection pump is too low, the spinning efficiency will decrease and the spinning solution will easily coagulate; if the injection speed is too fast, the spinning solution will flow too fast and cannot be stretched into filaments under the action of the electric field force; the spinning time will affect the thickness of the fiber membrane. The shorter the spinning time, the smaller the thickness, and the longer the spinning time, the greater the thickness.
[0047] In the preferred embodiment of the preparation method of the shape memory super-hydrophobic anticorrosive coating for marine metal of the present invention, in step (3), super-hydrophobic coating solution is sprayed on the surface of nanofiber composite coating by air pressure spraying, and the air pressure during air pressure spraying is 0.5-1.2atm (for example, 0.5atm, 0.7atm, 0.9atm, 1.1atm or 1.2atm), spray gun is 6-10cm (for example, 6cm, 8cm or 10cm) away from coating surface, spraying time is 15-25s (for example, 15s, 20s or 25s), and spraying number is 1-3 times (for example, 1 time, 2 times or 3 times). Wherein, if air pressure is too small, modified diatomite particles cannot be sprayed on the surface of nanofiber composite coating; if air pressure is too large, the pressure during spraying will be too large, then the coating morphology will be destroyed.
[0048] In a preferred embodiment of the method for preparing a shape memory super-hydrophobic anti-corrosion coating for marine metal of the present invention, the material of the metal substrate is at least one of carbon steel, magnesium alloy, aluminum alloy, copper and titanium alloy.
[0049] The present invention also proposes a shape memory super hydrophobic anti-corrosion coating for marine engineering metals. The shape memory super hydrophobic anti-corrosion coating for marine engineering metals in an embodiment of the present invention is prepared by the method described above.
[0050] The surface of the shape memory super hydrophobic anti-corrosion coating for marine engineering metal of the present invention presents a higher contact angle, a lower sliding angle, and a lasting super hydrophobic property; the nanofiber composite coating has a shape memory effect, and when the coating is damaged, it only needs to be heated to restore the original surface morphology (this allows the shape memory super hydrophobic anti-corrosion coating for marine engineering metal of the present invention to greatly reduce the contact area and contact time between the coating and water molecules during use, which is beneficial to preventing corrosive media and the like from penetrating the coating).
[0051] The shape memory super hydrophobic anti-corrosion coating for marine engineering metals of the present invention has a wide range of applications, has good adhesion, water resistance, and salt water penetration resistance after being cured into a film, and has multiple self-healing properties, a simple process, and has excellent anti-corrosion effects and lasting protective capabilities.
[0052] In addition, the shape memory super hydrophobic anti-corrosion coating for marine metal of the present invention can be used in seawater environment above 50°C. In a preferred embodiment of the present invention, the self-healing of the coating can be achieved by heating at 50°C for 2 hours; therefore, if the shape memory super hydrophobic anti-corrosion coating for marine metal of the present invention is applied to a seawater environment with a relatively high temperature, it is helpful to achieve the self-healing of the coating without heating the coating or reducing the heating pressure on the coating, better guarantee the protective effect of the coating on the marine metal, improve the service life of the marine metal, and reduce the maintenance frequency of the marine metal anti-corrosion coating.
[0053] The present invention also provides a marine engineering metal equipment. The surface of the marine engineering metal equipment in the embodiment of the present invention is provided with the shape memory super hydrophobic anti-corrosion coating as described above.
[0054] The following is a detailed description of the machine preparation method and application of the shape memory super hydrophobic anti-corrosion coating for marine engineering metals of the present invention through specific embodiments.
[0055] In the following embodiments:
[0056] The particle size of the diatomaceous earth used is 20±5μm; octadecyltrimethoxysilane (analytical grade) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; tetraethyl silicate (analytical grade), polycaprolactone (molecular weight 80,000), bisphenol A diglycidyl ether (analytical grade), neopentyl glycol diglycidyl ether (analytical grade) and n-decylamine (analytical grade) were purchased from Shanghai MacLean Biochemical Co., Ltd.; E44 oily epoxy resin and low molecular weight polyamide curing agent (matching E44 oily epoxy resin) were purchased from Zhenjiang Danbao Resin Co., Ltd.; N,N-dimethylformamide (analytical grade), dichloromethane (analytical grade), anhydrous ethanol and sodium chloride were purchased from Sinopharm Chemical Reagent Co., Ltd.; Q235 carbon steel was purchased from Shandong Shengxin Technology Co., Ltd.
[0057] Example 1
[0058] This embodiment provides a method for preparing a shape memory super hydrophobic anti-corrosion coating for marine metal, comprising the following steps:
[0059] (1) Preparation of modified diatomite:
[0060] Weigh 5 g of diatomaceous earth powder, dissolve it in 60 mL of anhydrous ethanol and stir, add 2 g of octadecyltrimethoxysilane thereto after stirring evenly, and heat the mixed solution to 40 ° C., stir for 8 h, and then stir it at room temperature for 12 h, then filter and wash it three times with ethanol, and put the obtained powder in an oven at 60 ° C. for 12 h to obtain a super hydrophobic powder (i.e., modified diatomaceous earth);
[0061] (2) Preparation of spinning solution:
[0062] Under the conditions of temperature of 20° C. and humidity of 25%, 25 g of a mixed solution was prepared (dichloromethane and N,N-dimethylformamide were stirred until uniformly mixed to obtain a mixed solution; the mass ratio of dichloromethane to N,N-dimethylformamide in the mixed solution was 3:1);
[0063] Weigh 5 g of polycaprolactone particles and add them to the mixed solution (i.e., the first solvent), adjust the temperature to 40° C., and continue stirring for 16 hours to obtain a spinning solution for later use;
[0064] (3) Preparation of nanofiber composite coating on carbon steel:
[0065] First, prepare the resin coating. Bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether and n-decylamine are mixed in a weight ratio of 2:1:1, and evenly coated on the metal substrate (carbon steel) with a glass rod. Apply it three times and place it in an oven at 40°C for 10 minutes. When the coating reaches a surface dry state, the coating thickness is 40 μm.
[0066] Then, the syringe filled with spinning solution is fixed on the electrostatic coaxial spinning machine, the coaxial needle is connected to the positive and negative power supplies, a piece of aluminum foil is covered on the collector, and the metal substrate carbon steel coated with resin coating is fixed on the aluminum foil; the spinning voltage is adjusted to 10kV, the pushing speed of the injection pump is 0.5mm / min, the temperature is 20℃, and the humidity is 30%; the spinning time is 45 minutes, and the nanofiber composite coating is obtained;
[0067] (4) Preparation of shape memory super hydrophobic anticorrosion coating:
[0068] Weigh 2g E44 oily epoxy resin and 1.5g low molecular weight polyamide curing agent, dissolve in 12g anhydrous ethanol, stir for 20min, add 4g modified diatomaceous earth, stir again for 20min, place the solution in a spray gun, and spray it on the surface of the nanofiber composite coating with air pressure of 1atm, the spray gun is 12cm away from the coating surface, the spraying time is 15s, the number of spraying is 3, and then placed in a 30℃ oven for 4h to finally obtain a shape memory superhydrophobic anti-corrosion coating. The thickness of the final composite coating is 70μm.
[0069] Example 2
[0070] This embodiment provides a method for preparing a shape memory super-hydrophobic anti-corrosion coating, which is different from Embodiment 1 only in that the metal substrate is replaced by aluminum alloy from carbon steel; the other steps and parameters are the same as those in Embodiment 1.
[0071] Example 3
[0072] The difference between this embodiment and embodiment 1 is that the amount of ethanol solution used in step (1) is 15 mL; the rest is consistent with embodiment 1.
[0073] Example 4 The difference between this example and Example 1 is that the amount of ethanol solution used in step (1) is 30 mL; the rest is consistent with Example 1.
[0074] Example 5
[0075] The difference between this embodiment and embodiment 1 is that the amount of octadecyltrimethoxysilane used in step (1) is 0.5 g; the rest is consistent with embodiment 1.
[0076] Example 6
[0077] The difference between this embodiment and embodiment 1 is that the mass ratio of dichloromethane to N,N-dimethylformamide in the 25 g mixed solution weighed in step (2) is 1:1; the rest is consistent with embodiment 1.
[0078] Example 7
[0079] The difference between this embodiment and embodiment 1 is that the mass ratio of dichloromethane to N,N-dimethylformamide in the 25 g mixed solution weighed in step (2) is 5:1; the rest is consistent with embodiment 1.
[0080] According to tests, the self-healing temperature of the coating of this embodiment is above 70°C.
[0081] Example 8
[0082] The only difference between this embodiment and embodiment 1 is that the amount of polycaprolactone used in step (2) is 2 g; the rest is consistent with embodiment 1.
[0083] According to tests, the self-healing temperature of the coating of this embodiment is above 70°C.
[0084] Example 9
[0085] The only difference between this embodiment and embodiment 1 is that the amount of polycaprolactone used in step (2) is 6 g; the rest is consistent with embodiment 1.
[0086] According to tests, the self-healing temperature of the coating of this embodiment is above 70°C.
[0087] Example 10
[0088] The difference between this embodiment and embodiment 1 is that in step (3), the mass ratio of bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether and n-n-decylamine is 1:1:1; the rest is consistent with embodiment 1.
[0089] According to tests, the self-healing temperature of the coating of this embodiment is above 70°C.
[0090] Embodiment 11
[0091] The difference between this embodiment and embodiment 1 is that in step (3), the mass ratio of bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether and n-n-decylamine is 1:2:1; the rest is consistent with embodiment 1.
[0092] According to tests, the self-healing temperature of the coating of this embodiment is above 70°C.
[0093] Example 12
[0094] The only difference between this embodiment and embodiment 1 is that the amount of modified diatomaceous earth used in step (4) is 1 g; the rest is consistent with embodiment 1.
[0095] Example 13
[0096] The only difference between this embodiment and embodiment 1 is that the amount of the low molecular weight polyamide curing agent used in step (4) is 0.8 g; the rest is consistent with embodiment 1.
[0097] Comparative Example 1
[0098] This comparative example provides a method for preparing a pure resin coating, and the steps are as follows:
[0099] To prepare the resin coating, bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether and n-decylamine were mixed in a weight ratio of 2:1:1, and evenly coated on a metal substrate (carbon steel) with a glass rod. The coating was applied three times and placed in an oven at 60°C for 20 minutes. When the coating reached a surface dry state, a pure resin coating was obtained, and the coating thickness was 43 μm.
[0100] Comparative Example 2
[0101] This comparative example provides a method for preparing a nanofiber composite coating, which is different from Example 1 only in that step (1) and step (4) are not involved, and the other steps and parameters are the same as those in Example 1.
[0102] Comparative Example 3
[0103] This comparative example provides a method for preparing a nanofiber composite coating, which differs from Example 1 only in that the preparation of the resin coating in step (3) is not involved (the bisphenol A epoxy resin and the curing agent are not coated on the metal substrate), the electrospun fibers are directly collected on the metal substrate, and then step (4) is performed. The other steps and parameters are the same as those in Example 1.
[0104] Comparative Example 4
[0105] This comparative example provides a method for preparing a nanofiber composite coating, which is different from Example 1 only in that no oily epoxy resin and low molecular weight polyamide curing agent are added in step (4), and the modified diatomaceous earth is directly dissolved in anhydrous ethanol and then sprayed with air pressure. The other steps and parameters are the same as those in Example 1.
[0106] Application Examples
[0107] The performance tests were performed on the anti-corrosion coatings prepared in Example 1, Comparative Example 1 and Comparative Example 2:
[0108] 1) Scanning electron microscope (SEM)
[0109] Each sample was subjected to gold spraying and its surface was observed under a scanning electron microscope ( Figure 1 ).in, Figure 1 (a) is a pure resin coating (i.e., comparative example 1), the surface is very smooth, and no micro-nano structure is observed; Figure 1 (b) is a nanofiber composite coating (Comparative Example 2), in which the intricate fibers can be clearly seen, and the diameter of the fibers is relatively uniform, forming a good surface morphology; Figure 1 (c) is the morphology after the super-hydrophobic coating solution is sprayed on the surface of the nanofiber composite coating (Example 1). The disc shape unique to diatomaceous earth can be clearly seen, and there are holes on the surface of the disc. The entire surface presents a micro-nano layered structure, and the particles are agglomerated.
[0110] 2) Confocal microscope (CLSM)
[0111] The sample was placed under a laser confocal microscope to observe the roughness of the coating surface ( Figure 2 ).in, Figure 2 (a) is the coating of comparative example 1, the surface is very smooth, the roughness is 2.137 μm, and the coating is hydrophilic at this time; Figure 2 (b) is a nanofiber composite coating (Comparative Example 2), which has sporadic protrusions on the surface and is slightly rough. The fibers form a relatively rough surface with a roughness of 4.213 μm. At this time, the coating is hydrophilic; Figure 2 (c) is a shape memory super hydrophobic anti-corrosion coating (Example 1), the surface of which is accompanied by large particle protrusions, and the coating surface presents a micro-nano structure, which is a phenomenon caused by the agglomeration of diatomaceous earth particles. The roughness is significantly increased to 23.07 μm, and the coating is super hydrophobic at this time.
[0112] 3) Wettability test
[0113] Figure 3 The water contact angle diagrams of the coatings obtained in Example 1 and Comparative Example 2 at different times; Figure 2 and Figure 3 Combined with the results, it was found that as the roughness of the coating increased, the water contact angle of the coating became larger and larger. Figure 3 (b) shows the fiber composite coating prepared in Comparative Example 2. Its water contact angle is 65.4° at the beginning. When the water droplet is in contact with the surface for 18 seconds, the water contact angle drops to 34.2°, indicating that the wettability of the coating is hydrophilic and the water droplet penetration speed is fast. This is because the fiber surface is accompanied by a large number of hydroxyl groups and has a high porosity. When in contact with water, it will immediately combine with the water molecules on the surface, thus becoming hydrophilic.
[0114] and Figure 3(a) The shape memory super hydrophobic anticorrosion coating prepared by Example 1, its water contact angle is 163.2 ° at the beginning, after being in contact with water molecules for 40min, the water contact angle only drops by 4.1 °, drops to 159.1 °, still super hydrophobic. At this time, the coating is a hydrophobic layer formed by the coating formed by the nanofiber composite coating prepared by Comparative Example 2 and the super hydrophobic coating solution (containing modified diatomaceous earth and oleoresin). In general, Comparative Example 2 is inclusive with Example 1, and the lower layer of the shape memory super hydrophobic anticorrosion coating of Example 1 is the nanofiber composite coating of Comparative Example 2. It can be seen that the shape memory super hydrophobic anticorrosion coating of Example 1 has lasting water repellency.
[0115] 4) Pull-out test
[0116] Figure 4 Shown are the peeling adhesion strengths of different coatings to metal substrates.Quantitatively, the adhesion strength of pure resin coating (Comparative Example 1) is 0.21MPa, while the adhesion strengths of nanofiber composite coating (Comparative Example 2) and shape memory super hydrophobic anticorrosive coating (Example 1) to steel plates are 0.29MPa and 3.14MPa respectively.Results show that the coating formed after the super hydrophobic coating solution containing modified diatomite and oily epoxy resin is sprayed can effectively improve the adhesion strength of the coating as a whole to metal substrates.Compared with other coatings, the adhesion strength of Example 1 improves more significantly, which is related to the high compatibility and stable dispersion of modified diatomite in oily epoxy resin.
[0117] 5) Electrochemical impedance spectroscopy
[0118] The electrolyte was 3.5% NaCl solution, the reference electrode was saturated silver / silver chloride electrode, the counter electrode was carbon rod, the test amplitude was 10mV, the test frequency was 10 -2 Hz-10 5 Hz, electrochemical impedance spectroscopy was performed using a Parstat P4000+ electrochemical workstation (see Figure 5 ).
[0119] Depend on Figure 5 (a)( Figure 5 (a): the horizontal axis is LogF, i.e. the logarithm of frequency; the vertical axis is Log|Z|, i.e. the logarithm of modulus value). It can be seen that after immersion for 45 days, the impedance of the shape memory superhydrophobic anticorrosive coating (Example 1) can still reach 10 10 Ω·cm 2 The coating is still hydrophobic and can block the penetration of water molecules and corrosive media, thus having a strong protective ability for the metal substrate. The impedance of the pure resin coating (Comparative Example 1) is reduced to 10 4 Ω·cm 2This is because the pure resin coating is hydrophilic and easily combines with water molecules, with a large contact area. As the immersion time increases, water molecules and corrosive ions will penetrate into the metal surface through the micropores on the coating surface, causing corrosion of the metal. Once corrosion occurs, the coating will begin to peel off and gradually lose its protective ability.
[0120] Depend on Figure 5 (b1) and (b2) Figure 5 (b1) and (b2): the horizontal axis is Zre, i.e. the real part; the vertical axis is -Zim, i.e. the negative number of the imaginary part) It can be seen that after immersion for 45 days, the radius of the capacitive reactance arc of the shape memory superhydrophobic anti-corrosion coating (Example 1) is much larger than the radius of the capacitive reactance arc of the pure resin coating (Comparative Example 1). This is because the shape memory superhydrophobic anti-corrosion coating (Example 1) itself has strong mechanical properties and excellent hydrophobic durability, so the anti-corrosion performance does not decrease significantly with the extension of the immersion time. It can be seen that the shape memory superhydrophobic anti-corrosion coating (Example 1) has significantly better protection ability for metals than the pure resin coating (Comparative Example 1).
[0121] 6) Wear resistance test
[0122] The wear resistance of the coating surface provided in Example 1 was measured by withstanding the wear of 600-grit sandpaper under a load of 120 grams, with a wear distance of 25 cm and a total of 100 cycles of wear. The test results are as follows: Figure 6 As shown. Figure 6 It can be found in (a1)-(a4) that after 100 sandpaper abrasions, the loose nanoparticles deposited on the original surface are removed under mechanical linear motion, and the larger protrusions are also smoothed. The nanoparticles remaining on the surface are firmly adhered to the surface by the resin, indicating that the resin can tightly adhere the nanoparticles to the surface. These results prove that the shape memory superhydrophobic anticorrosive coating for marine metal provided in Example 1 has good wear resistance, and can still maintain relatively excellent protection performance and superhydrophobic performance under strong mechanical external force.
[0123] 7) Self-healing test
[0124] Figure 7(a)-(b) show the CLSM images of the crack area of the coating before and after the shape memory super hydrophobic anti-corrosion coating of Example 1 was repaired at 50°C for 2h. From Figure (a), it can be clearly observed that there is a crack on the coating surface, and the roughness on both sides of the crack is also affected. For the scratched coating surface, the scratch is completely closed after heating, leaving only a small gap, and the deformed area around the scratch is basically restored to its original shape (b). It shows that when heated above Tg (glass transition temperature), the fixed switch segment of the shape memory coating is reactivated and the entropy elastic behavior is restored, so that the deformed micro-nano structure is restored to the original shape defined by chemical cross-linking (dots). Therefore, the introduction of the nanofiber composite coating gives the super hydrophobic coating the property of self-healing.
[0125] Figure 8 ( Figure 8 The numbers “1”, “3”, “5”, “7”, “9” and “12” outside the center axis position refer to the number of damage / repair, respectively; Figure 8 In (a), the horizontal axis is LogF, i.e. the logarithm of frequency; the vertical axis is Log|Z|, i.e. the logarithm of modulus; Figure 8 (b1) and (b2): the horizontal axis is Zre, i.e. the real part; the vertical axis is -Zim, i.e. the negative number of the imaginary part) show the EIS test results after the coating is damaged and repaired. In addition to the corrosion inhibition effect of the coating itself, the corrosion resistance of the coating in the present invention is also repaired by the thermally induced shape memory effect. The coating of Example 1 was first artificially damaged with a scalpel, and then the coating was placed in a 50°C oven for healing for 2 hours (to achieve the repair of the damaged coating), and then immersed in a 3.5wt% NaCl solution, and the corrosion resistance of the coating was studied using the EIS test.
[0126] At the beginning of immersion, the Bode plots (modulus value Bode plots) of all coatings are characterized by a 45° straight line, |Z| 0.01Hz The value (i.e., the impedance value at a frequency of 0.01 Hz) reaches 2.5×10 10 Ω·cm 2 The above indicates that the coating has completely healed the damaged area through heat treatment after damage, thereby restoring its anticorrosion performance. This result is attributed to the heat-induced shape memory effect, the damaged area is perfectly healed, almost the same as the coating before damage, and the restoration of the air film in the convex structure restored by the superhydrophobic surface. The experiment proved that after the coating was damaged / repaired 12 times, |Z| 0.01Hz The value remains at 10 10 Ω·cm 2The above results show that the coating prepared by the present invention has the function of multiple repairs, which is significantly superior to the traditional single external self-repairing coating. After being damaged / repaired 12 times, the coating still maintains excellent corrosion resistance. According to these results, it has been confirmed that the shape memory superhydrophobic anti-corrosion coating for marine metals of the present invention can serve as a reliable barrier and provide stable and long-lasting superhydrophobicity.
[0127] 8) The adhesion strength, water contact angle, roughness and impedance of the coatings prepared in the examples and comparative examples were measured respectively. The results are shown in Table 1 below.
[0128] Table 1
[0129]
[0130]
[0131] Notes: (1) Since the water contact angles of Examples 3-5 are much smaller than 150°, the adhesion strength and impedance of Examples 3-5 were not tested; (2) Since no oily epoxy resin was added to Comparative Example 4, the modified diatomaceous earth could not be bonded to the surface of the nanofiber composite coating. Therefore, the modified diatomaceous earth would fall off during the curing process of the coating, thereby reducing the water contact angle, while the roughness did not change significantly; (3) The samples of Example 1 and Comparative Example 2 in Table 1 are the samples prepared by the methods of Example 1 and Comparative Example 2, respectively. Figure 3 The samples of Example 1 and Comparative Example 2 are located at different positions.
[0132] 9) The impedance of the coatings of Example 1 and Example 2 after damage / repair was tested respectively, and the test results are shown in Table 2 below:
[0133] Table 2
[0134]
[0135] Note: (1) The samples of Example 1 and Example 2 in Table 2 refer to samples prepared by the methods of Example 1 and 2, respectively, and located at different positions from those of Example 1 and 2 in Table 1; (2) The experimental data in Table 2 are for Figure 8 Obtained after fitting.
[0136] To sum up: the shape memory super hydrophobic anti-corrosion coating for marine engineering metals of the present invention has improved density, more uniform thickness and composition, better compatibility with the metal substrate, improved the defect of poor mechanical properties of the nanofiber membrane, and gives the super hydrophobic coating the characteristic of multiple self-healing; the shape memory super hydrophobic anti-corrosion coating for marine engineering metals of the present invention has excellent anti-corrosion and mechanical properties, and has a better protective effect on the metal substrate.
[0137] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a shape memory super hydrophobic anti-corrosion coating for marine metals, characterized in that: The steps include: (1) Preparation of bisphenol A resin coating: Bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether and n-decylamine are uniformly mixed to obtain a resin coating solution, and the resin coating solution is coated on a metal substrate. After the resin coating solution reaches a surface dry state, a metal substrate coated with a bisphenol A resin coating is obtained; the mass ratio of bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether and n-decylamine is (1-4):(1-3):1; (2) Preparation of nanofiber composite coating: Electrospinning is performed on the surface of a metal substrate coated with a bisphenol A resin coating to obtain the nanofiber composite coating; the components of the electrospinning solution include a first solvent and polycaprolactone; (3) Preparation of shape memory super hydrophobic anticorrosion coating: Spraying a super-hydrophobic coating solution on the surface of the nanofiber composite coating to obtain the shape memory super-hydrophobic anti-corrosion coating; the components of the super-hydrophobic coating solution include modified diatomaceous earth, oily epoxy resin, a curing agent and a second solvent; The modified diatomaceous earth is prepared by a method comprising the following steps: dispersing natural diatomaceous earth in a third solvent, stirring evenly, adding octadecyltrimethoxysilane, heating to a first temperature and stirring for a first time, then continuing to stir for a second time at room temperature, filtering, washing and drying to obtain the modified diatomaceous earth; the mass ratio of the natural diatomaceous earth to the octadecyltrimethoxysilane is 1:1-10:
1.
2. The method for preparing a shape memory super hydrophobic anticorrosive coating for marine metal according to claim 1, characterized in that: In step (3), the mass ratio of the oily epoxy resin to the modified diatomaceous earth is 1:2-1:10, the mass ratio of the oily epoxy resin to the curing agent is 2:1-1:1, and the mass ratio of the oily epoxy resin to the second solvent is 1:8-1:16; The second solvent is anhydrous ethanol.
3. The method for preparing a shape memory super hydrophobic anticorrosive coating for marine metal according to claim 1, characterized in that: During the preparation of the modified diatomite, the mass volume ratio of the natural diatomite to the third solvent is 1:(11-12), the mass of the natural diatomite is measured in g, and the volume of the third solvent is measured in mL; The first temperature is 35-60° C., and the first time is 8-16 hours; The second time is 6-12h; The third solvent is ethanol.
4. The method for preparing a shape memory super hydrophobic anticorrosive coating for marine metal according to claim 1, characterized in that: The spinning solution is prepared by a method comprising the following steps: A. mixing N,N-dimethylformamide and dichloromethane at a temperature of 18-25° C. and a humidity of 20%-30% to obtain a first solvent; B. adding polycaprolactone to the first solvent; C. Raise the temperature to 35-60°C and continue stirring for 12-18 hours to obtain the spinning solution.
5. The method for preparing a shape memory super hydrophobic anticorrosive coating for marine metal according to claim 4, characterized in that: In the first solvent, the mass ratio of N,N-dimethylformamide to dichloromethane is 1:1-1:6; The mass ratio of the polycaprolactone to the first solvent is (2-6):
25.
6. The method for preparing a shape memory super hydrophobic anti-corrosion coating for marine metal according to claim 1, characterized in that: In step (2), the preparation of the nanofiber composite coating comprises the following steps: fixing a syringe containing a spinning solution on an electrostatic coaxial spinning machine, connecting the coaxial needle to positive and negative power supplies, covering a collector with an aluminum foil, fixing a metal substrate coated with a bisphenol A resin coating on the aluminum foil, and performing electrostatic spinning; The voltage of the electrospinning is 7-12 kV, the pushing speed of the injection pump is 0.4-0.8 mm / min, and the spinning time is 20-40 min; The electrospinning is carried out under the condition of humidity of 20%-30%.
7. The method for preparing a shape memory super hydrophobic anti-corrosion coating for marine metal according to claim 1, characterized in that: In step (3), the super-hydrophobic coating solution is sprayed on the surface of the nanofiber composite coating by air pressure spraying, the air pressure during the air pressure spraying is 0.5-1.2atm, the spray gun is 6-10cm away from the coating surface, the spraying time is 15-25s, and the number of spraying times is 1-3 times.
8. The method for preparing a shape memory super hydrophobic anti-corrosion coating for marine metal according to any one of claims 1 to 7, characterized in that: The material of the metal matrix is at least one of carbon steel, magnesium alloy, aluminum alloy, copper and titanium alloy.
9. A shape memory super hydrophobic anti-corrosion coating for marine metals, characterized in that: The shape memory super hydrophobic anti-corrosion coating for marine engineering metal is prepared by the method according to any one of claims 1 to 8.
10. A marine metal equipment, characterized in that: The surface of the marine metal equipment is provided with a shape memory super hydrophobic anti-corrosion coating as described in claim 9.
Citation Information
Patent Citations
Preparation method of fluorocarbon resin / polycaprolactone-based self-healing super-hydrophobic coating
CN115502068A
Double-sided nanometer fiber composite coating as well as preparation method and application thereof
CN117139113A
Nanofiber toughening organic coating doped with hydrophobic particles as well as preparation method and application of nanofiber toughening organic coating
CN117701100A
Preparation method of self-repairing super-hydrophobic anti-scaling corrosion inhibition coating suitable for marine metal
CN117946573A
Cited By
Self-healing super-hydrophobic corrosion-resistant composite coating as well as preparation method and application thereof
CN120118592A
High-orientation super-hydrophobic bionic anti-icing anticorrosive coating and preparation method thereof
CN121652645A
